EVALUASI IMPLEMENTASI TEKNOLOGI INFORMASI MENGGUNAKAN MODEL COBIT FRAMEWORK 5.0 (STUDI KASUS: POLITEKNIK LP3I JAKARTA) - Fadli, Ahmad (POLITEKNIK LP3I JAKARTA, 2018)
AbstractThis research aims to discuss about condition of information technology governance at 16 of campus Politeknik LP3I Jakarta. This research aims to determine the extent to which 16 of campus Politeknik LP3I Jakarta have implemented good IT governance. This research focused only on the two dominant COBIT 5.0 PO and ME consists of 96 detailed control objectives while the AI and DS domain has been judged to meet the standards of good management of information technology is at level 3 (defined). Whilst the instrument rated by supervisors themselves, interviews and direct observation to collect the data. The third method is based on the Model COBIT 5.0. The data processing will be used to look for the weaknesses found in each domain. The finding weaknesses or problems will be compared with the ideal conditions that have been set COBIT 5.0 at each level, so that it can be seen that suitable recommendations to be implemented. The main problem encountered is the management do not understand the importance of investing in information technology, risk management has not been well managed, and ability SDM are still lacking. Control technology resulting in a weak, high cost of information technology is not accompanied by a return value in improving the effectiveness, efficiency and profits.Keywords: COBIT 5.0, information technology governance, Politeknik LP3I Jakarta